THE ABILITY OF THE FIRST YEARS STUDENTS IN MASTERING VOCABULARY AT SMP NEGERI 10 PALOPO - Reski, Pilu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2016)
The objective of the research is to find out the ability of the first year students at SMP Neg. 10 palopo in mastering vocabulary. This research is descriptive research that will be analyzed qualitatively. It describes the ability of the students of SMP Negeri 10 Palopo in mastering vocabulary. The population of this research will be the first year students of SMP Negeri 10 Palopo. Findings of the research in vocabulary test shows that most of students got score in poor classification namely 21 and 7 got fairly poor. This fact implies that most of the student had low ability in vocabulary at SMPN 10 Palopo. Only 1 student got fairly and one got fairly good. No one got good, very good and excellent.